Phthalocyanines prepared from 4,5-dihexylthiophthalonitrile, a popular building block - ŞAHİN, ZEYNEL; İŞCİ, ÜMİT (My University, 2023)
Phthalocyanines are tetrapyrrolic artificial porphyrinoids that play major roles in advanced biological and technological applications. Research on this family of dyes is particularly active in Türkiye, with many derivatives being prepared from 4,5-dihexyl-thiophthalonitrile DiSHexPN, which is one of the most popular noncommercially available building blocks for phthalocyanines. This review summarizes the phthalocyanines and their versatile properties and applications that have been published since 1994, when the synthesis of DiSHexPN was first described, to emphasize the importance of this building block in plentiful applications, all with biomedical or technological impact.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; hexylthio; Phthalocyanine; phthalonitrile; Phthalocyanine; phthalonitrile; hexylthio